2009
DOI: 10.1111/j.1365-3164.2008.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the nature and pathogenicity of circulating antikeratinocyte antibodies in dogs with pemphigus foliaceus

Abstract: In humans with pemphigus foliaceus (PF), pathogenic autoantibodies are principally of IgG4 subclass and they cause superficial vesiculation when injected into neonatal mice. The objectives of this study were to determine the isotypes of circulating antikeratinocyte antibodies in dogs with PF, to assess whether serum antikeratinocyte antibody titres decreased during successful treatment, and to study whether such antibodies were pathogenic in passive transfers. Using indirect immunofluorescence with neonatal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 28 publications
2
35
2
Order By: Relevance
“…For comparative laboratory investigations, archived skin biopsy‐containing paraffin‐embedded blocks from 10 dogs with spontaneous autoimmune PF (AIPF) were retrieved. These cases were selected because of a clinical phenotype of facial‐predominant, erosive and crusted dermatitis, microscopic demonstration of neutrophil‐rich pustules containing numerous acantholytic keratinocytes and circulating antikeratinocyte IgG autoantibodies as described previously 4 . In these 10 dogs, there had been no history of drug administration compatible with the diagnosis of drug‐associated PF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparative laboratory investigations, archived skin biopsy‐containing paraffin‐embedded blocks from 10 dogs with spontaneous autoimmune PF (AIPF) were retrieved. These cases were selected because of a clinical phenotype of facial‐predominant, erosive and crusted dermatitis, microscopic demonstration of neutrophil‐rich pustules containing numerous acantholytic keratinocytes and circulating antikeratinocyte IgG autoantibodies as described previously 4 . In these 10 dogs, there had been no history of drug administration compatible with the diagnosis of drug‐associated PF.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate whether antikeratinocyte antibodies were present in the serum of affected patients, blood was collected from selected cases, whenever possible, and isolated sera were kept frozen until testing at North Carolina State University. Indirect IF was performed, as done routinely in our laboratory, 4 using both normal canine footpad and buccal mucosa as substrates. The titre of IgA antikeratinocyte membrane autoantibodies was determined starting at 1:10, with doubling dilutions until extinction of any positive signal.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it is important to note that an association between epidermal-specific auto-antibodies and complement proteins has been described previously in human pemphigus (Lessey et al, 2008;Qian et al, 2011); a cross-reaction among IgE, IgM, and IgG4 anti-DSG-1 response has been reported in human PF patients (Qian et al, 2011). In contrast, IgM autoreactivity was not detected when canine PF serum was used against either DSG-1 or DSC-1 (Bizikova et al, 2014), and canine PF showed dominant IgG auto-antibody reactivity (Pérez et al, 2002: Olivry et al, 2009). Moreover, a previous study also detected IgM-producing B-cells in the extracellular matrix of the dermis and in the intercellular epidermis in canine PF (Pérez et al, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the IgM auto-antibody response may be less predominant than the IgG response or it may correspond to cross-reactivity in individual dogs with pemphigus. Immunostaining for IgG, IgG1 and IgG4 was predominant in the stratum granulosum of PF dogs which probably correlates with disease activity as IgG auto-antibodies have been shown to cause blister formation in the skin of experimental mice by passive transfer of IgG antibodies (Olivry et al, 2009). Similarly, abundant mast cells in the pustules of pruritic skins were observed in feline PF (Preziosi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Desmoglein‐1 (DSG1), the second critical desmosomal protein in the upper epidermis and the major target autoantigen in human PF, appears to be recognized by only a minority of tested dogs with PF . Although the pathogenic significance of anti‐DSC1 or anti‐DSG1 IgG autoantibodies in canine PF has not yet been demonstrated, the pathogenic nature of the total antikeratinocyte IgG has been documented by passive transfer experiments in neonatal mice …”
Section: Introductionmentioning
confidence: 99%